Developing TOEFL-Based Vocabulary Building Materials for The Students of IAIN Palangka Raya - Widiastuty, Hesty; Qamariah, Zaitun; Ali Mirza, Akhmad (IKIP Siliwangi, 2025)
This research aimed to design and develop TOEFL-based vocabulary-building materials for students at IAIN Palangka Raya. The research addresses the need for specialized English instructional materials for TOEFL preparation. Existing TOEFL preparation resources are often generic and not tailored to the specific needs of Indonesian students. The purpose of this research is to create materials grounded in the KKNI framework to enhance students' proficiency in reading, writing, listening, speaking, vocabulary, and grammar. Data were gathered through needs analysis, reference studies, material development, expert validation, and tryouts using observations, questionnaires, and interviews. The developed materials include sequences of tasks designed to incrementally build the language skills required for the TOEFL. Expert validation and empirical try-outs confirmed that the materials effectively address students' needs and support TOEFL preparation. This research demonstrates a systematic approach to developing targeted instructional materials that fill a gap in available TOEFL resources. Using these materials is expected to improve students' lexical knowledge and lead to higher TOEFL scores, providing a model for data-driven development of instructional materials based on local contexts.